Contemporary Visual Art Practices - Antoniou, Klitsa (My University, 2026)
The Contemporary Visual Art Practices Lab of the Fine Arts Department at Cyprus University of Technology was established in 2019 by Klitsa Antoniou. It aims to promote research, theory, art and fine arts practices, as well as explore the role of Empathy in Contemporary Visual Arts in the making of creative and effective works of art within the context of Contemporary political and social issues. Established collaborations with the following Centers and Museums